2018
DOI: 10.3389/fphy.2018.00059
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Molecular Dynamics Simulation of Plasma Processing: Application to Plasma Sputtering

Abstract: Molecular dynamics is an atomistic tool that is able to treat dynamics of atom/molecules/cluster assemblies mainly in the condensed and liquid phases. The goal of the present article is to provide a new methodology for describing all phenomena of plasma processing and beyond such as gas phase chemistry as well. Simulations of condensed matter and liquid processes by molecular dynamics are now readily accessible provided the interaction potentials are available, so quantitative parameters can be deduced as diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…The latter is only true within a fixed energy flux, otherwise the energy distribution allows gas phase collisions [10,14]. Recently, Brault [17] demonstrated the gas phase clustering using a multi-scale MD simulation, i.e. when the deposition flux travels a distance similar to that in a typical experiment, with gas phase collisions treated properly.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is only true within a fixed energy flux, otherwise the energy distribution allows gas phase collisions [10,14]. Recently, Brault [17] demonstrated the gas phase clustering using a multi-scale MD simulation, i.e. when the deposition flux travels a distance similar to that in a typical experiment, with gas phase collisions treated properly.…”
Section: Methodsmentioning
confidence: 99%
“…So far the target side simulations are focused on the sputter yield and energy distribution of ejected atoms from the target [15,16]. Recently, Brault [17] included the working gas between target and deposition sides within a multi-scale MD simulation. He suggested that the effect of the gas phase in sputter deposition is limited to the narrowing of the energy distribution as atoms travel towards the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The height of the space between the target and the electrode was chosen to mimic an experimental argon pressure of 7.5 Pa for an experimental target to substrate separation of 6.5 cm. Applying the equality of collision numbers in the simulation box and the experiment [13,18] led to a height of 120 nm and 17,388 Argon atoms. The corresponding simulation box is drawn in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, many synthesis techniques such as plasma sputtering deposition have been investigated, including conventional magnetron, high-power impulse magnetron sputtering, and magnetron gas aggregation source depositions [4][5][6][7]. Since these deposition processes are of atomic nature, the description and insights into targeted growth processes to improve NP morphology, structure, and properties can successfully be explored using atomistic simulations, especially molecular dynamics [8][9][10][11][12][13][14][15][16]. Both growth in inert and reactive plasma environments has, thus, been shown feasible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation